Closing the gaps: Steps towards elimination of mother-to-child transmission of HIV - Mary Ibeto; Janet Giddy; Vivian Cox (AOSIS, 2014)
Background. With significant reductions in the rate of HIV mother-to-child transmission (MTCT) in South Africa, each case of failed prevention of MTCT (PMTCT) should be investigated.  Objective. To establish the cause(s) of MTCT at Khayelitsha's Community Health Centre (CHC) in order to identify obstacles to MTCT elimination. Methods. Routinely collected data were reviewed for all HIV-infected infants identified at Khayelitsha Site B CHC from January 2012 to April 2013. Results. A total of 926/1 158 (80%) of exposed infants had polymerase chain reaction (PCR) results, with 15/926 (1.6%) PCR-positive. Median (interquartile range (IQR)) values for the maternal indicators were as follows: maternal age, 27 (23 - 31) years; parity, 2 (1 - 3); gestational age at antenatal presentation, 21.5 (17.5 - 30.5) weeks; CD4+, 377(219 - 446) cells/µl. Of the 15 PCR-positive infants, five received ART, five received AZT and five received no prophylaxis. Viral loads were not monitored for any of the women receiving antenatal ART. Nine of the 15 (60%) delivered in hospital, with 6/9 requiring caesarean section. The median (IQR) infant birth weight was 3.0 (2.6 - 3.5) kg. All received prophylactic nevirapine post exposure. Two of the 15 were clinically unwell at birth, and 14 (86.7%) were breastfed, with 10 (66.7%) recorded as exclusively breastfed. Median (IQR) time between delivery and PCR results was 6.6 (6.1 - 7.3) weeks.  Discussion. PMTCT programmes must consider each PCR-positive infant as a sentinel event that can provide valuable insight into correcting ongoing clinical and programmatic reasons for HIV transmission. The main risk factors for MTCT identified in this study were late presentation for antenatal care, inadequate antenatal PMTCT prophylaxis and a lack of viral load monitoring.